Kesadaran Intuitif Plus Cahaya Ilahiyah; Husserl di Muka Cermin Suhrawardi - Mohammad Muslih (TSAQAFAH, 2009)
Husserl has introduced intuitive consciousness in order to see directly the complexity and reality without devise and perspective. In Western thought, Husserl’s view is considered as strange up to the present time. The basic problem of Suhrawardi is similar with Husserl, indeed validity of knowledge, in which the only authority is at the Peripatetic logic. The main characteristics of this scientific model are the truth of syllogism, proposition, concept and problem of definition. This article tries to relate between Husserl’s view on intuitionalism and Suhrawardi’s view on illumination, even still based on preliminary experiment. The unity of Husserl and Suhrawardi seems to be gigantic power. “Intuitionalism under the light of God.” Can be an alternative. On the other hand, it also may be as a solution for the ontological view on reality which nowadays tend to be materialistic and mechanical. The view of this mechanical materialistic factually raises various crises on the modern life. Ontologically, the light of Intuitionalism can be the basis of the development of thought at different aspects of life, such as ethic, esthetic, anthropology, epistemology, etc.